Strong Sensitivity of Pine Island Ice-Shelf Melting to Climatic Variability - Dutrieux, Pierre; De Rydt, Jan; Jenkins, Adrian; Holland, Paul R.; Ha, Ho Kyung; Lee, Sang Hoon; Steig, Eric J.; Ding, Qinghua; Abrahamsen, E. Povl; Schröder, Michael (Science, 2014)
Cold Glacier Growth Pine Island Glacier in Antarctica has thinned significantly during the last two decades and has provided a measurable contribution to sea-level rise as a result. Both glacier dynamics and climate are thought to be responsible for thinning, but exactly how they influence the glacier are incompletely known. Dutrieux et al. (p. 174 , published online 2 January) provide another layer of detail to our understanding of the process through observations of ocean temperatures in the surrounding waters. The thermocline adjacent in the sea adjacent to the glacier calving front (where ice is discharged) lowered by 250 meters in the austral summer of 2012. This change exposed the bottom of the ice shelf to colder surface waters rather than to the warmer, deeper layer, thereby reducing heat transfer from the ocean to the overlying ice and decreasing basal melting of the ice by more than 50% compared to 2010. Those 2012 ocean conditions were partly caused by a strong La Niña event, thus illustrating how important atmospheric variability is for regulating how the Antarctic Ice Sheet responds to climate change.